PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 67 PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Mardalena '; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : The problem in the research is student achievement still low, in study science subject at SD Negeri 67 Pematang Pudu Kecamatan Mandau Kabupaten Bengkalis of fourth grade. From 20 students at fourt grade who compieted as many as 8 student (40%) while not complete as many as 12 (60%) the average student who not complete with scor 58. This Research to improve student ability in sclences learning process fourth grade at SD Negeri 67 Pematang Pudu Kecamatan Mandau Kabupaten Bengkalis with implementation cooperative learning model Student Teams Achievement Division (STAD). Data collection instruments in this thesis is the activity sheet teacher, stdent avtivities sheets and achievement test. This research presents the results obtained from the value of learning with an average of 58 and after UH I cycle I increased to 64,5. After UH I cycle I improve student with scor 11,20%. In UH II cycle II the average of student 7,3. This improve student with scor 25,80%. Activity teacher improve student from scor 58,30% to 66,70% in cycle of teacher improve student with good category. In cycle II increased 83,30% to 95,80% with very good category. The results of study in fourth grade SD Negeri 67 Pematang Pudu Kecamatan Mandau Kabupaten Bengkalis proved that implementayion of cooperative learning model Student Teams Achiement Division (STAD) can improve the student. Key Word :       Cooperative Learning Model Type of Student Teams Achievement    Division (STAD), Science Students Achievement.